Measuring the volume charge in dielectric films using single frequency electro-acoustic waves. Issue 4 (3rd March 2014) - Pei, Dongfei; Shkel, Yuri M.; Klingenberg, Daniel J.; Segal, Zakai I.; Nishi, Yoshio; Shohet, J. Leon
Abstract: Abstract : An electro-acoustic method for measuring volume charge distributions in dielectric films (50 μm–0.2 mm thick) is described. A high voltage (>1 kV) sinusoidal signal (frequency ∼ 2 kHz) is applied across the dielectric sample. The charges inside the dielectric material will mechanically respond to the input electric signal and excite acoustic waves. The acoustic waves can be detected and measured using a piezoelectric sensor. By analyzing the received acoustic signal, we are able to compare the amount of charge in various samples.